The Concept of The Ideal State and Its Implications For Contemporary Leadership Education - Alkhadafi , Rahmad (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
The purpose of this paper is to explore the principles of education in Plato's ideal state concept and its implications to leadership education in the contemporary era. This research uses a qualitative method based on literature search. The research found that Plato's ideal state is based on education and virtue, with the main goal of creating justice and happiness for all people. Plato formulated an ideal state led by a philosopher, who has the intellectual capacity and high morality to manage the state fairly. Plato strongly emphasized the importance of education in an ideal state, with education will make people moral, able to think critically and systematically. Plato viewed education as the main foundation for producing superior individuals, not only in terms of intellect, but also in terms of morality and ethics. His philosophical education aims to create individuals with wisdom (sophia), courage (andreia), self-control (sophrosyne), and justice (dikaiosyne). These four values are the main pillars in producing leaders who are wise and able to act in the interests of society fairly. In the contemporary context, this approach can be applied through an education system that emphasizes character development, critical thinking, and a deep understanding of ethical values.